Insulin degludec/insulin aspart is the first co-formulation of basal and prandial insulin analogues - Ivan Ivanovich Dedov; Marina Vladimirovna Shestakova (Сахарный диабет)
Achievement of glycemic control is the major therapeutic aim to prevent or delay the onset and progression of diabetes related complications. Insulin therapy represents a cornerstone in the treatment of diabetes and has been used widely for achieving glycemic goals. The aim for insulin therapy is to mimic the physiological profile of insulin secretion seen in nondiabetic patients. Development of the insulin analogs has offered new opportunities in the diabetes management to achieve greater safety and tolerability of diabetes treatment. Insulin degludec/insulin aspart(IDegAsp) (Ryzodeg?, Novo Nordisk, Denmark) is the first soluble co-formulation of 70% ultra-long acting insulin degludec and 30% rapid-acting prandial insulin aspart, providing both basal insulin coverage and a prandial insulin bolus in a single injection. This review discusses data regarding the efficacy, safety, tolerability and clinical benefits of IDegAsp. According to the clinical development program IDegAspprovides an achievement of similar glycemic control with superiority in lowering FPG with using less number of injections and lower daily insulin dose, and also associated with numerically lower rates of confirmed and nocturnal confirmed hypoglycaemia in comparison with premixed or basal insulin analogues, as well as a basal component for basal?bolus therapy with supplementary mealtime insulin aspart.Trial results suggest that IDegAspQD or BID maybe an appropriate and reasonable option for initiating insulin therapy in type 1 and type 2 diabetic patients inadequately controlled on maximal doses of oral antidiabetic drugs,and also a simple alternative to basal?bolus treatment in patients who require intensification of insulin therapy, especially when adherence to more complex regimens is challenging.